Power, Responsibility, and Sexually Violent War Tactics: a Theoretical and Empirical Analysis of Rape During Civil War - (:unkn) unknown (My University, 2017)
Broadly, this dissertation asks, why rape? In address, this research posits a leadership preference-based strategic theory of rape during war; marking the first large-N, quantitative exploration of leadership preferences on the use of rape in civil war. Using an original dataset, preferences of armed group leaders are evaluated against the level of rape across all civil conflicts between 1980 - 2009. The results highlight three critical findings. First, evidence suggests that rape is distinctive from other human rights violations and is permitted or controlled differently than are more common forms of extra-combat violence (i.e., torture, extra-judicial killings, disappearances). This work argues that the symbolic meaning of rape, given its gendered nature and uniquely devastating outcomes, makes it a particularly attractive tool of war under some conditions. Second, statistical tests reveal that different factors predict state-perpetrated rape than predict rebel-perpetrated rape; with the strongest predictive power across rebel groups in ethnic war. Finally, results illustrate that the predictive power of the models is conditioned by the type of war. That is, provided the characteristics of ethnic war, models perform better in predicting rape in ethnic war than in non-ethnic war.
Keywords: Comparative Politics; Feminist Studies; Human Rights; International Relations; Rape; War